Social and community inclusion outcomes for adults with autism with and without intellectual disability in Australia. Issue 7 (8th June 2022) - Cameron, L. A.; Tonge, B. J.; Howlin, P.; Einfeld, S. L.; Stancliffe, R. J.; Gray, K. M.
Abstract: Background: Research suggests that adults with autism tend to have poor outcomes. Outcomes have mostly been defined using summary outcome ratings, with less focus on specific outcomes such as employment, living situation, social satisfaction, loneliness, and friendships. This study aimed to explore social and community outcomes, including employment, education, living arrangements, friendships, and social satisfaction, for autistic adults with and without intellectual disability. Method: Eighty‐four adults with autism (mean age 34.2 years, SD = 4.5; 67% with co‐occurring intellectual disability), recruited as children and adolescents, participated in the current study. Adult social and community inclusion outcomes were explored through interview and questionnaire, both parent/carer‐report and self‐report. Results: Participants predominantly lived with family or in supported accommodation, did not pursue higher education, and mostly participated in day activity programmes. Most had limited friendships as reported by parents/carers; however, self‐report data ( n  = 28) indicated that adults were largely satisfied with their social relationships. Overall outcome was poor for 57%, and good / very good for 34%. Adults with intellectual disability generally had poorer outcomes. Conclusion: Autistic adults encountered numerous difficulties in leading an independent life. Adults with co‐occurring intellectual disability were most likely to experience difficulties; however, outcomes ranged from poor to very good for adults without intellectual disability. Discrepancies in parent/carer‐report and self‐reported experiences of friendships highlight the need to ensure individual experiences are captured in addition to parent/carer‐report. Appropriate resources and programmes are crucial for adults with autism to support them to have the choice to live independently.